MOTIVASI KOMUNIKASI TRANSAKSIONAL ANTARA ELIT POLITIK DENGAN MASYARAKAT AGRARIS PADA PEMILIHAN KEPALA DAERAH - Muhammad Zein Abdullah (Journal Publicuho, 2021)
This study aims to find and explain the motivation for transactional communication between the political elite and the agrarian community in the 2015 Pilkada in North Konawe Regency. Data collection techniques through interview instruments, shadowing techniques by following the political elite, participatory observation, Focus Group Discussion (FGD), and documentation studies.The results showed that the motivation for transactional communication between the political elite and the agrarian society was: (1) Political Interest Motivation. Political elite motivation for power. (2) Motivation of social relations. The motivation of political elites and agrarian society due to family (clan) (3) Regional proximity motivation: Regional faction that regional proximity was formed in the political sphere in the 2015 election in North Konawe to give rise to regional factions. (4) Motivation for Social and Cultural Relations. (5) The economic motivation of the Agrarian Society is to increase economic investment in agriculture through the development of regional infrastructure, agricultural technology, land clearing, capital assistance, the opening of farm roads, fertilizers, seeds, electricity and so on.